To the knowledge of cuckoo wasps (Hymenoptera: Chrysididae) of the Balearic Archipelago, Spain - Strumia, Franco; Gayubo, Severiano Fernández (Zootaxa, 2013)
The Chrysididae of the Balearic Archipelago were studied by operating four Malaise traps in the Mallorca and Menorca Islands. Traps captured 98 individuals belonging to 19 species. Including all available data from literature, the number of species in this archipelago rise to 34. Hedychridium balearicum Strumia, sp. nov (Mallorca) is described and key to the Hedychridium monochroum species-group is given. Extrapolation from available data suggests the presence of about 58 to 107 Chrysididae species in the Balearic Archipelago.